Methylenetetrahydrofolate reductase C677T and A1298C polymorphisms and fluorouracil-based treatment in Taiwan colorectal cancer. Issue 8 (September 2015) - Wu, Nai-Chun; Su, Shih-Ming; Lin, Tai-Jung; Chin, Jen; Hou, Chun-Fang; Yang, Jhong-Ying; Liu, Wen-Sheng; Chang, Li-Ching
Abstract : This study aimed to investigate the association between methylenetetrahydrofolate reductase ( MTHFR ) gene polymorphisms and the prognosis of colorectal cancer (CRC) patients undergoing 5-fluorouracil (5-FU)-based chemotherapy in Taiwan. We investigated 126 CRC cases. The most common polymorphisms C677T (rs1801133) and A1298C (rs1801131) in MTHFR were genotyped using PCR-restriction fragment length polymorphism. The frequencies of C677T and A1298C were further compared with those in the HapMap database for Whites and Asians. In this study, we found that TT-homozygosity at MTHFR C677T was significantly associated with survival in CRC patients [ P <0.001; 95% confidence interval (CI)=0.068–0.212]. In CRC patients receiving 5-FU-based chemotherapy, the TT genotype at C677T was also significantly associated with survival ( P =0.001; 95% CI=0.113–0.400) and recurrence after surgery ( P <0.001; 95% CI=0.295–0.609). The A1298C genotypes had a significant impact on survival ( χ 2 =7.103; P =0.029). The MTHFR A1298C CC genotype may increase the risk of death in Taiwanese CRC patients. The MTHFR C677T TT genotype was present at a lower frequency in our CRC patients than in the HapMap Asian population, but the frequency was similar to that in Whites in the HapMap database. The distribution of MTHFR A1298C genotypes was similar in our CRC and in the HapMap Asian population, but was different from that in the White population. This study suggested that MTHFR C677T and A1298C are associated with prognosis in CRC patients undergoing 5-FU-based chemotherapy.